Bem dito e bem feito: a dimensão espetacular das performances narrativas de feirantes rurais do alto Jequitinhonha - Alves, Rafael Lorran (2015)
After two centuries since the emancipation of the main cities in the Alto Vale do Jequitinhonha / MG, the traditional rural fairs in the region maintain the dynamic flow of subjects, their wares and stories. Through observations of narrative events recorded in the logbook, audio and video from December 2012 to August 2014 propose a theoretical review that understands the spectacular dimension of narrative performances of rural fairground of high Jequitinhonha Valley. Using the Etnocenologia as research perspective, adding the looks methodological approaches of theatrical anthropology, phenomenology and sociology of the body, I wonder about the concepts of narrative performance, spectacular behavior, memory, body, oral and spatiality in order to better understand the social interactions and . aesthetic evident in the storytelling of four cities farmers (Itamarandiba, Tourmaline, Carbonita and Aricanduva) and the rural district area of Canjuru This study is divided into three sections: the first presents the universe of this research, a brief ethnography of orality Jequitinhonha, spaces and memories that make up the stories and subjects; the second discusses the implications on the performance and spectacle, analyzing the mechanisms and behaviors of narrators observed in the field, and the third session and present an imagery raid sound, guided by the Link youtube video accompanying this work in order to better approach the spectacular phenomenon of the player that is the experience of orality in Jequitinhonha.